Co-existence of five- and six-coordinate iron(ii) species captured in a geometrically strained spin-crossover Hofmann framework. Issue 25 (7th June 2022) - Xu, Luonan; Xie, Zixi; Zenere, Katrina A.; Clegg, Jack K.; Kenny, Elise; Rijs, Nicole J.; Jameson, Guy N. L.; Kepert, Cameron J.; Powell, Benjamin J.; Neville, Suzanne M.
Abstract : The use of an angular ligand drives the formation of an irregular Hofmann framework whereby 6-coordinate and rare 5-coordinate Fe II species co-exist – the 6-coordinate species show a spin-crossover transition. Abstract : Inclusion of an angular bridging ligand, 4, 2′:6′, 4′′-terpyridine (TPy), into a Hofmann-type framework produces an irregular network in which six- and five-coordinate Fe II species co-exist. The octahedral sites show thermally-induced spin-crossover (SCO) and the rare five-coordinate Fe II sites are high-spin.